Intracranial arterial wall imaging using three-dimensional high isotropic resolution black blood MRI at 3.0 Tesla - Qiao, Ye; Steinman, David A.; Qin, Qin; Etesami, Maryam; Schär, Michael; Astor, Brad C.; Wasserman, Bruce A. (Journal of magnetic resonance imaging, 2011)
Purpose: To develop a high isotropic‐resolution sequence to evaluate intracranial vessels at 3.0 Tesla (T). Materials and Methods: Thirteen healthy volunteers and 4 patients with intracranial stenosis were imaged at 3.0T using 0.5‐mm isotropic‐resolution three‐dimensional (3D) Volumetric ISotropic TSE Acquisition (VISTA; TSE, turbo spin echo), with conventional 2D‐TSE for comparison. VISTA was repeated for 6 volunteers and 4 patients at 0.4‐mm isotropic‐resolution to explore the trade‐off between SNR and voxel volume. Wall signal‐to‐noise‐ratio (SNRwall), wall‐lumen contrast‐to‐noise‐ratio (CNRwall‐lumen), lumen area (LA), wall area (WA), mean wall thickness (MWT), and maximum wall thickness (maxWT) were compared between 3D‐VISTA and 2D‐TSE sequences, as well as 3D images acquired at both resolutions. Reliability was assessed by intraclass correlations (ICC). Results: Compared with 2D‐TSE measurements, 3D‐VISTA provided 58% and 74% improvement in SNRwall and CNRwall‐lumen, respectively. LA, WA, MWT and maxWT from 3D and 2D techniques highly correlated (ICCs of 0.96, 0.95, 0.96, and 0.91, respectively). CNRwall‐lumen using 0.4‐mm resolution VISTA decreased by 27%, compared with 0.5‐mm VISTA but with reduced partial‐volume‐based overestimation of wall thickness. Reliability for 3D measurements was good to excellent. Conclusion: The 3D‐VISTA provides SNR‐efficient, highly reliable measurements of intracranial vessels at high isotropic‐resolution, enabling broad coverage in a clinically acceptable time. J. Magn. Reson. Imaging 2011;. © 2011 Wiley‐Liss, Inc.